Emergency medical preparedness and response for mass gatherings: Papua New Guinea emergency medical team's experience during Pope Francis's 2024 visit - Oli, Ulysses; Nou, Garry G; Hosea, Rose; Konigala, Kelvin (Western Pacific Surveillance and Response, 2026)
Problem: Papua New Guinea has hosted several mass gatherings in recent years. Yet, there is limited data on the involvement of emergency medical teams in these events, let alone in other low- and middle-income countries. Prior to Pope Francis’s state visit in September 2024, the national emergency medical team (EMT) had not simulated its updated clinical patient flow systems.Context: During Pope Francis's visit, an estimated 70 000 attendees gathered at the national stadium. Using Arbon’s mass gathering model, the patient presentation rate was calculated to be 330 over 2 days, or 4.7 per 1000, posing a significant challenge to local health-care capacity.Action: The National Department of Health mobilized its EMT to lead clinical operations in collaboration with the National St. John Ambulance service. Planning spanned 6 weeks and involved provincial partners.Outcome: Over 2 days, 257 patients, or 3.7 per 1000, were managed using a hub-and-spoke model. First-aid stations operated by the St. John Ambulance service treated 200 patients for dehydration and headaches, while the Advanced Casualty Management Centre handled 57 cases of heat-related illnesses and chronic condition exacerbations.Discussion: The deployment of the EMT showcased its capability and credibility, setting a national milestone and providing a feasible model for mass-gathering preparedness and response in low- and middle-income countries in the World Health Organization’s Western Pacific Region. This report highlights not only the importance of multipartner collaboration in such preparedness, providing baseline data for low-resource settings, but also the scalability of rehabilitation services and the Interagency Integrated Triage Tool as frameworks for future deployments.
Keywords: Papua New Guinea; emergency responders; disaster planning; mass gathering; emergency medical team